SERBUK GERGAJIAN KAYU JATI (Tectona grandis) SEBAGAI BAHAN PENGAWET KAYU DURIAN (Durio zibethinus) - Sulaiman Bakri; Adie Fahriza; Budi Tri Cahyana (Kementerian Perindustrian, 2012)
Durian wood (Durio zibethinus) from unproductive trees is a potential source of wood as raw material for furniture industry, but it has the weakness of vurnability to the wood insects such as dry wood termites. The objective of research is to find out the effectiveness of sawdust extract of teak wood (Tectona grandis) in preventing the decaying of durian wood. Thus the effort can improve the properties of durian wood. The preservative used in the research is extract of teak sawdust, i.e 250 gr/5 l water, 500 gr/5 l water and 750 gr/5 l. The preservation is used by cold soaking to the solution resulted from extraction for 7 days. The result of research shows that the application of teak sawdust for 500 gr/5 l water is sufficiently effective, because it causes the mortality of dry wood termites for 100,00 % and the retention of 17, 01 mg/cm3.Keywords: teak sawdust, durian wood, natural preservatives, mortality, retention.